The importance of strategic analysis in investment appraisal - Moutinho, Nuno (2020)
The investment of a company allows the creation of shareholder value, so an adequate analysis of all factors that may interfere with its viability is relevant. For the evaluation of a given project, financial criteria and non-financial criteria should be used. Here we highlight the importance of the strategic aspects for the investment decision and highlight the importance of the synergies and the consistency with the strategic objectives of the company. We also present the main strategic risks and how to minimize them.